Circadian rhythm disruption with high‐fat diet impairs glycemic control and bone quality. Issue 9 (19th August 2021) - LLabre, Joan E.; Trujillo, Ruben; Sroga, Grażyna E.; Figueiro, Mariana G.; Vashishth, Deepak
Abstract: Biological functions, including glycemic control and bone metabolism, are highly influenced by the body's internal clock. Circadian rhythms are biological rhythms that run with a period close to 24 hours and receive input from environmental stimuli, such as the light/dark cycle. We investigated the effects of circadian rhythm disruption (CRD), through alteration of the light/dark schedule, on glycemic control and bone quality of mice. Ten‐week‐old male mice (C57/BL6, n = 48) were given a low‐fat diet (LFD) or a high‐fat diet (HFD) and kept on a dayshift or altered schedule (RSS3) for 22 weeks. Mice were divided into four experimental groups (n = 12/group): Dayshift/LFD, Dayshift/HFD, RSS3/LFD, and RSS3/HFD. CRD in growing mice fed a HFD resulted in a diabetic state, with a 36.2% increase in fasting glucose levels compared to the Dayshift/LFD group. Micro‐CT scans of femora revealed a reduction in inner and outer surface expansion for mice on a HFD and altered light schedule. Cancellous bone demonstrated deterioration of bone quality as trabecular number and thickness decreased while trabecular separation increased. While HFD increased cortical bone mineral density, its combination with CRD reduced this phenomenon. The growth of mineral crystals, determined by small angle X‐ray scattering, showed HFD led to smaller crystals. Considering modifications of the organic matrix, regardless of diet, CRD exacerbated the accumulation of fluorescent advanced glycation end‐products (fAGEs) in collagen. Strength testing of tibiae showed that CRD mitigated the higher strength in the HFD group and increased brittleness indicated by lower post‐yield deflection and work‐to‐fracture. Consistent with accumulation of fAGEs, various measures of toughness were lowered with CRD, but combination of CRD with HFD protected against this decrease. Differences between strength and toughness results represent different contributions of structural and material properties of bone to energy dissipation. Collectively, these results demonstrate that combination of CRD with HFD impairs glycemic control and have complex effects on bone quality.